Character of Apai Saloi in Iban Folktales - Syaryfah Fazidawaty, Wan Busrah; Khairul Aidil Azlin, Abdul Rahman; Anna, Durin (UNIMAS Publisher, 2018)
Apai Saloi is a comic hero in Iban folktales. Back in the old days, Apai Saloi folktales are often told to youngsters by an elderly caretaker at night. This kind of folktales contains lots of moral value in it. Based on the preliminary study done, Apai Saloi is famous with his foolish and stupid deeds. The objective of this paper is to investigate on the character of Apai Saloi in selected documented Iban folktales because the looks and characteristics of Apai Saloi was remained unknown. This paper explains in detail the analysis of Apai Saloi in 15 stories to measure what is major characteristic of Apai Saloi by using conceptual method in determining the highest ranking of Apai Saloi characteristic in the selected documented stories. Finding shows that Apai Saloi character is proven to have a significant characteristic that was able to pull the interest of the targeted members of the readers. The study will provide new possibilities to be further developed to form a character design of Apai Saloi to present Iban culture to a greater audience and most importantly to promote local culture as well as to educate people from in and out of Sarawak about the importance of preserving local content.